Development of a Project Based Learning Arabic Curriculum to Improve the Quality of Learning Arabic for 8th Grade Students at Junior Islamic High School Amdadiyah Kediri - Ratna Sa'idah; Qintan Emilia Sholihah; Moh Sholeh Afyuddin; Bagus Andrian Permata (Asalibuna, 2022)
Based on the facts, it shows that teachers are still using the old model curriculum and students are still having difficulties in learning Arabic and there is a need for the development of a new curriculum. So that here researchers will develop a new learning curriculum, namely the Arabic language learning curriculum based on project-based learning. The researcher chose a project-based learning Arabic learning curriculum because it can increase learning motivation, improve problem-solving skills, increase collaboration and improve skills in managing resources.This research uses a type of research and development or what is commonly called research and development (R&D). This research method aims to develop a particular product or create a new product accompanied by a test of the effectiveness of the product. The development model used is the ADDIE model (Analyze, Design, Develop, Implement and Evaluate). This research and development is based on researchers who will develop an Arabic language learning product, namely a project-based learning Arabic curriculum. Small-group or limited-group trials were carried out at MTs Amdadiyah Kediri. Therefore, a curriculum with various activities is needed that can develop students' creativity in completing assignments. Product trials are carried out by validation tests and field tests. The results of the validation test by curriculum experts I and II obtained an average R (Percentage of agreement) value of the validator of 81,53%. The normality test used is the Shapiro-Wilk. The significance value (Sig.) in the Shapiro-Wilk pre-test and post-test was above (p > 0.05), so based on the Shapiro-Wilk normality test the data was normally distributed. That is, there was no decrease (reduction) and as many as 22 students experienced an increase in Arabic scores after participating in learning activities that implemented a project-based learning Arabic learning curriculum. As for the results of the questionnaire on the responses of class VIII MTs Amdadiyah students to the application of the Arabic language curriculum based on project-based learning, they obtained a percentage of 86.06% which was categorized as "very feasible".